Pendampingan Perhitungan Harga Pokok Produksi Kursi dan Meja Yang Dihasilkan Insan Difabel Di SLB Paedagogia Surabaya - Maria Widyastuti; Stefanus Prabani; Mei Kristiani Haref (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity is a continuation of 2022, the Paedagogia SLB Vocational School which is managed by the Kaliasin Education Foundation in Surabaya which specifically pays attention to people with disabilities so that they have skills. After training, mentoring and empowering people with disabilities, there has been good collaboration between people with disabilities and the implementing team so that the transfer of knowledge is easy to accept so that the lamination process to unite the chair and table components can run smoothly until the finished product, namely chairs and tables. In the next stage, mentoring is carried out for teachers to calculate the cost of chair and table products as a basis for determining the selling price. Cost of production consists of three types of costs: 1) Direct raw materials 2) Direct labor 3) Factory overhead costs. The results of the calculation of the three cost components show that the cost of production for one chair or one table is IDR 359,805 and the shipping costs are borne by the seller. Meanwhile, the selling price depends on the desired profit.